2022
DOI: 10.1186/s13054-022-04190-y
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory alterations in critically ill COVID-19 patients analyzed using artificial intelligence

Abstract: Background The sublingual microcirculation presumably exhibits disease-specific changes in function and morphology. Algorithm-based quantification of functional microcirculatory hemodynamic variables in handheld vital microscopy (HVM) has recently allowed identification of hemodynamic alterations in the microcirculation associated with COVID-19. In the present study we hypothesized that supervised deep machine learning could be used to identify previously unknown microcirculatory alterations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Indeed, the reported crude mortality ranged from 23% to 33% for vaccinated patients and 22% and 29% for unvaccinated patients. 15,16 In Italy, because of safety concerns, a substantial number of individuals were vaccinated with…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the reported crude mortality ranged from 23% to 33% for vaccinated patients and 22% and 29% for unvaccinated patients. 15,16 In Italy, because of safety concerns, a substantial number of individuals were vaccinated with…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Two multicenter studies conducted in Spain and Switzerland reported that fully vaccinated patients with COVID-19 admitted to an ICU had more comorbidities, greater exposure to immunosuppressive drugs, lower ICU length of stay but similar ICU mortality compared with unvaccinated patients. 15,16 However, in both studies, the number of vaccinated and unvaccinated patients admitted during the Alpha and Delta variant waves may have been unbalanced.…”
Section: Introductionmentioning
confidence: 97%
“…To bridge the gap from research to clinical application for microcirculatory monitoring, the application of artificial intelligence is an emerging field of interest. Previously, Hilty et al showed that a deep learning-based model successfully differentiates critically ill COVID-19 patients from healthy volunteers in sublingual microcirculation microscopy [30]. Due to its technical features to analyze tissue morphology and composition, HSI is increasingly evaluated for automated artificial intelligence applications [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that AI will play a central role in the translation of the evaluation of the clinical condition of the virtual patient and to predict response to clinical interventions. This is achievable, for example, for the case of the microcirculation, by integrating AI methodologies with algorithmic analysis of microcirculatory images able to differentially diagnose specific alterations in the phenotype of the microcirculation known to be corrected by specific therapeutic interventions [ 53 ]. AI will allow to have a global vision of macrocirculatory and microcirculatory parameters and to better analyze their response to interventions.…”
Section: What Evidence Is Needed To Facilitate Adoption Of Microcircu...mentioning
confidence: 99%